The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1111/1365-2745.14111
|View full text |Cite
|
Sign up to set email alerts
|

Soil nutrients cause threefold increase in pathogen and herbivore impacts on grassland plant biomass

Abstract: Grasslands play a critical role in the global carbon (C) cycle, covering a quarter of the Earth's land surface and contributing up to 20% to the total terrestrial C sink (Xia et al., 2014). As with most ecosystems, C accumulation in grasslands reflects the balance and seasonal variation of C inputs via photosynthesis (gross primary production, GPP) and C emissions from respiration by microbes, plants and animals (ecosystem respiration, ER). Observational studies and field experiments manipulating food webs hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…2014; Dybzinski & Tilman, 2007;Eskelinen et al, 2022). Previous work in this experiment found that more biomass is allocated above than belowground following nutrient addition pointing to a potential shift in competition for light (Zaret et al, 2023). Overall forbs had the largest range of responses to consumer and nutrient manipulations and C4 grasses the least (Figure 4).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…2014; Dybzinski & Tilman, 2007;Eskelinen et al, 2022). Previous work in this experiment found that more biomass is allocated above than belowground following nutrient addition pointing to a potential shift in competition for light (Zaret et al, 2023). Overall forbs had the largest range of responses to consumer and nutrient manipulations and C4 grasses the least (Figure 4).…”
Section: Discussionmentioning
confidence: 69%
“…Under higher resource scenarios, consumers are predicted to have modified impacts on plant hosts due to a variety of mechanisms ranging from modified susceptibility or immunity in plants to herbivory or infection (Smith, 2007) as well as microbes and herbivores changing consumption strategies and preference among hosts under increased nutrients (Peters et al, 2006). Previous work in this system shows amplified foliar fungal and arthropod impacts on plant biomass in fertilized plots (Zaret et al, 2023), suggesting that a shift toward poorly defended species following nutrient addition (reflecting the growth-defense trade-off) has implications for ecosystem processes such as carbon cycling. Studies integrating defense trade-offs and ecosystem processes in the context of global changes such as increasing nutrient supplies would help clarify this knowledge gap.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Grazing by livestock influences the productivity and stability of grassland ecosystems, which in turn generates feedback mechanisms on the carbon cycle. However, the factors underlying the complex changes of vegetation and soil as a result of grazing and their impact on the processes underlying carbon cycling remain poorly understood (Yuanet al 2011;Hussain et al 2015;Oram et al 2023;Zaret et al 2023). Our results from a 16-year long grazing intensity manipulation study in a desert steppe grassland show that grazers alter patterns of net ecosystem exchange primarily via their negative influence on the biomass of shrub and semi-shrub, which play a prominent role in ecosystem functions.…”
Section: Discussionmentioning
confidence: 99%
“…Heterotrophs include herbivores, predators, scavengers, and pathogens. Previous studies showed that the removal of arthropods and foliar fungi increased plant biomass [ 8 , 9 , 10 ], while the removal of soil fungi increased the forb biomass in grassland systems [ 11 ]. Removing foliar fungi also increased the biomass of trees in forest systems [ 12 ].…”
Section: Introductionmentioning
confidence: 99%